Social Capital in the Implementation of Food Diversification Policy: A Systematic Review With Bibliometric Analysis - Akbar, M; Alwi, ‎; Susanti, Gita; Ibrahim, Muhammad Akmal (KnE Social Sciences, 2025)
This study aims to map and analyze the development of global scientific literature related to the role of social capital in food diversification policy implementation during the period from 2019 to 2025. Using a bibliometric approach based on the Scopus database, this study compiles a quantitative analysis of 163 selected documents through co-word techniques, field distribution, and geographic collaboration mapping. Results show a significant upward trend in the number of annual publications, especially post-COVID-19, as attention to community-based food security increases in response to the global food system crisis. The thematic distribution shows the dominance of contributions from social, agricultural, and environmental sciences, confirming the multidisciplinary character of the study. Indonesia recorded the largest number of contributors geographically, followed by the United States, China, and Australia, with a strong tendency towards contextualized, local community-based approaches. Keyword analysis identified a concentration of themes on community empowerment, sustainable food security, and participatory governance. Theoretically, the findings suggest that social capital functions not just as an enabling variable, but rather as a structural determinant in food policy effectiveness, particularly within the framework of polycentric and transformative governance. The main contribution of this study lies in systematically mapping the position of social capital in the food diversification discourse, as well as filling a void in the literature that has been dominated by technocratic and agronomic approaches. The practical implications of this study include the urgency of integrating social capital strengthening strategies into a more adaptive, participatory, and contextualized food policy design. This study also opens space for a further research agenda to explore the relational and institutional dimensions of social capital more deeply within the framework of equitable and sustainable food security